Quali-quantitative analysis of adherence and perceived satisfaction of individuals with COPD after high-intensity training on land and in water: additional analysis from a randomized clinical trial - Débora Rafaelli de Carvalho; Larissa Araújo de Castro; Myriam Fernanda Merli; Josiane Marques Felcar; Lais Silva Vidotto; Dirce Shizuko Fujisawa; Vanessa Suziane Probst (Universidade de São Paulo, 2021)
ABSTRACT Although patients with chronic obstructive pulmonary disease (COPD) benefit in many ways after participating in pulmonary rehabilitation programs, high dropout rates are still observed among participants. This study aims to analyze the adherence rate and perceived satisfaction in individuals with chronic obstructive pulmonary disease who underwent high-intensity physical training on land (LG) and in water (WG). This study is an additional analysis from a randomized controlled trial. In total, 36 subjects (51%) completed the intervention. All participants underwent six months of high-intensity endurance and strength training. Adherence was assessed by the proportion of patients who completed the training program. Perceived satisfaction was evaluated using a questionnaire composed of structured and semi-structured questions. The interviews were recorded, transcribed, and analyzed according to the criteria of our thematic analysis. The Shapiro-Wilk test was used to assess data normality, and dropout rates were compared using the chi-square test. Statistical significance was set at 5%. Regarding adherence, 59% of WG participants and 44% of LG participants completed the program, with no difference between the groups (p>0.05). Individuals from both groups were equally satisfied after six months of physical training (<90%); the therapist-patient relationship and treatment effectiveness being important factors for this perception. Qualitative analysis also showed that WG participants reported a more prominent improvement in their respiratory symptoms, leisure, sensation of pain, and sleep. In conclusion, patients with COPD were satisfied after six months of high-intensity physical training in water and on land, noting that water exercising promoted additional benefits compared to land exercising. There seems to be no superiority to any of the regimens (water or land) regarding the adherence to the training programs.